Implementa??o e an?lise num?rica de um modulador para sistema de HDTV usando a t?cnica das bandas laterais assim?tricas - Lima, Jos? de Souza (2004)
This work aims to present a digital modulator for High Definition Television (HDTV) in the 8-Level Vestigial Sideband (8-VSB) system, using the Weaver Method for modulation and although the work presents the results for the 8-VSB system , The same hardware can be used to generate modulated signals in the National Television System Committee (NTSC). Phase Alternating Line (PAL) or Systeme Electronique Couleur Avec Memoire (SECAM), in addition to allowing the inclusion of linear distortion pre-correction circuits, even in an adaptive way, obtaining results much higher than those obtained with the currently implemented technique in use.